Sustaining Long-Distance Relationship Through Love, Trust, and Dedication Among Married Couples - Joki Perdani Sawai; Mahirah Masdin; Rezki Perdani Sawai; Abdul Rashid Abdul Aziz (Pusat Penataran Ilmu dan Bahasa, 2024)
Non-Indexed Publication